Potential Strategies Applied by Metschnikowia bicuspidata to Survive the Immunity of Its Crustacean Hosts - Ji Zhang; Bingyu Li; Bingnan Zuo; Xiaodong Li (Pathogens)
Metschnikowia bicuspidata is the specific pathogen for “milky disease” in the Chinese mitten crab (Eriocheir sinensis), accounting for huge losses to the industry. And yet, there is no precise study describing the pathogenesis of M. bicuspidata, largely hindering the development of novel control methods against its causing diseases. Here, we compared the transcriptomes of M. bicuspidata cells collected from a control group (cultured without E. sinensis hemocytes) and a treatment group (cultured with E. sinensis hemocytes), using RNA sequencing. Through comprehensively analyzing the differentially expressed genes (DEGs), both the most regulated ones and the ones involved in crucial enriched KEGG pathways, we found that certain processes might be required for M. bicuspidata’s survival under hemocyte stress. Key genes involved in oxidative phosphorylation, fatty acid metabolism, upper glycolysis, and gluconeogenesis were upregulated, and those for β-glucan unmasking, autophagy, and cell polarity were downregulated, in the treatment group. Our results suggest that M. bicuspidata colonizes and therefore establishes an infection in E. sinensis via enhancing aerobic respiration, glucose-6-phosphate accumulation, and cell-wall masking. In addition, we applied multiple means to evaluate a series of candidate reference genes and found that PMA1 in combination with ACT1 is the most suitable choice for accurate normalization in quantitative real-time PCR (qRT-PCR) assays. Thus, we used this combination as the reference and performed qRT-PCR verification of several DEGs. It is shown that the expression trends of these tested DEGs in qRT-PCR assays are the same as those in RNA-Seq assays. This study not only provides insights into strategies facilitating M. bicuspidata’s survival within E. sinensis, initially elucidating the pathogenesis of this yeast, but also recommends a useful molecular tool regarding qRT-PCR assays in this pathogen.